How the Tourism Sector in Emerging Markets is Recovering from COVID-19 - Mekharat, Nisachol; Traore, Nouhoum (International Finance Corporation, Washington, DC, 2020)
Summary of Note 95, how the Tourism Sector in Emerging Markets is Recovering from COVID-19 Tourism is an important sector that accounts for 10 percent of global gross domestic product and one in every 10 jobs. As a result of COVID-19-related travel restrictions, the United Nations World Tourism Organization (UNWTO) has estimated that international tourist arrivals in 2020 will drop between 58 and 78 percent, which puts 100 to 120 million direct tourism jobs at risk. The effects of COVID-19 are felt throughout the extensive tourism value chain, including airlines, hotels, restaurants, tour operators, food suppliers, farmers, retailers, and a wide range of other small and medium enterprises. Although all tourist destinations strongly feel the impact from the pandemic-related crisis, not all have the same vulnerabilities or capacity to recover. This note explores the factors in specific tourism destinations that contribute to pandemic-related vulnerability, as well as the factors that support the resilience of the tourism sector. Examining all these factors together provides a snapshot of the countries as well as the subsectors that are most likely to recover first, as well as those that will require greater support to weather and recover from the crisis.